1994
DOI: 10.1002/elps.1150150195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the acute phase serum protein response in pigs

Abstract: Acute inflammation was induced in pigs using a single subcutaneous turpentine injection. The acute phase serum protein response was analyzed using crossed immunoelectrophoresis and immunodiffusion. The concentration of C reactive protein and haptoglobin increases 5-7 times 48 h after the injection, whereas the concentration of an alpha 2-globulin, named pig major acute phase protein (pig-MAP), increases at least 15-fold. A molecular mass of 115 kDa for pig-MAP was determined by sodium dodecyl sulfate-polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
101
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 17 publications
11
101
4
1
Order By: Relevance
“…Decreases in apo A-I concentration during acute phase processes have been described in other species [27,43], suggesting that it could be involved in the modulation of inflammation [1,6]. Slight decreases in albumin and transferrin concentrations were also observed in pigs after turpentine induced inflammation [21].…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Decreases in apo A-I concentration during acute phase processes have been described in other species [27,43], suggesting that it could be involved in the modulation of inflammation [1,6]. Slight decreases in albumin and transferrin concentrations were also observed in pigs after turpentine induced inflammation [21].…”
Section: Introductionmentioning
confidence: 80%
“…Studies have shown important variation in the APP response among species. APP were first characterised in humans [20], rodents [19,22] and later in other animal species, such as pigs [13,21]. Clinical use of APP determination has been proposed in veterinary medicine to determine the health status of farm animals in various production processes [14,28,39].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations